Peer Observation as a Professional Development Tool for English as a Foreign Language Teachers - Susi Handayani; Fithriani, Rahmah (JIE (Journal of Islamic Education), 2024)
This research examines EFL (English as a Foreign Language) teachers' perceptions of peer observation as a tool for developing professionalism. This research uses a qualitative approach, a case study type at Medan High School. The subjects of this research took two EFL teachers as English teachers. Data was obtained through observation and in-depth interviews. Then the data was analyzed using the Miles & Huberman data analysis model which includes data condensation, data presentation and verification or conclusion. The research results show teachers' positive perceptions of peer observation as a tool for teacher professional development. In developing teacher professionalism, peer observation can improve the quality of learning because correlation and input from peers can provide better teaching methods and innovation. It can also support reflection and develop understanding because it builds collaboration by involving colleagues in observing each other in a reciprocal process to improve classroom teaching through self-reflection. Peer observation brings many benefits to teachers. This helps teachers solve problems they face in teaching and provides learning opportunities to acquire new teaching methods or strategies from colleagues. Therefore, this research recommends that teachers conduct peer observations to develop their professionalism. Through peer observation, teachers receive constructive feedback to improve their teaching.